2020
DOI: 10.1002/ange.202005946
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of Catechols and Amines in High‐Performance Dry/Wet Adhesives

Abstract: The outstanding adhesive performance of mussel byssal threads has inspired materials scientists over the past few decades. Exploiting the amino‐catechol synergy, polymeric pressure‐sensitive adhesives (PSAs) have now been synthesized by copolymerizing traditional PSA monomers, butyl acrylate and acrylic acid, with mussel‐inspired lysine‐ and aromatic‐rich monomers. The consequences of decoupling amino and catechol moieties from each other were compared (that is, incorporated as separate monomers) against a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…The synergy between flanking Lys and Dopa has been frequently studied, suggesting that their synergy promotes underwater adhesion via salt displacement, water displacement, energy dissipation, and entropy compensation . Additionally, the amine–catechol synergy has been studied not only for theoretical models but also for designing practical pressure-sensitive adhesives that could be used in both dry and wet conditions . In this work, we, for the first time, tried to investigate how the proximity of amines and catechols affects cation−π interactions using a nanomechanical tool.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The synergy between flanking Lys and Dopa has been frequently studied, suggesting that their synergy promotes underwater adhesion via salt displacement, water displacement, energy dissipation, and entropy compensation . Additionally, the amine–catechol synergy has been studied not only for theoretical models but also for designing practical pressure-sensitive adhesives that could be used in both dry and wet conditions . In this work, we, for the first time, tried to investigate how the proximity of amines and catechols affects cation−π interactions using a nanomechanical tool.…”
Section: Discussionsupporting
confidence: 93%
“…46 Additionally, the amine−catechol synergy has been studied not only for theoretical models but also for designing practical pressuresensitive adhesives that could be used in both dry and wet conditions. 47 In this work, we, for the first time, tried to investigate how the proximity of amines and catechols affects cation−π interactions using a nanomechanical tool. Unexpectedly, we observed an antisynergetic effect of the Lys−Dopa pair on underwater cation−π interactions using synthetic simple peptides: Dopa with flanking Lys had weaker cation−π interactions than Dopa with separated Lys (Figure 3a).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our simulation ndings conrmed and claried the mechanism of hydrogen bonds formation for cohesive strength improvement resulting from DMA comonomer. 14,15 Mechanical properties Three methods including (1) static, (2) uctuation formula, and (3) dynamics are used to calculate mechanical properties using molecular dynamics results. 45 In this study, the static procedure was used to determine mechanical properties.…”
Section: Hydrogen Bondsmentioning
confidence: 99%
“…Tiu et al 14 reported that DMA comonomer improved the adhesion strength of poly( n -butyl acrylate- co -acrylic acid) copolymer to different organic and metal surfaces. Furthermore, they showed 15 that a combination of catechol and amino acid in a side group led to the highest improvement in the performance of the adhesive based on copolymers of poly( n -butyl acrylate- co -acrylic acid) in the peeling, static shear and atomic force spectroscopy tests. As a different approach, effect of hydroxyl and hydrogen group groups on the adhesion of liquid to substrate have been discussed in literature 16,17 by using fluorosilanes on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Many marine organisms such as mussels, sandcastle worms, and barnacles, can firmly anchor themselves to surfaces that are routinely covered with the undesired hydration layer . This fascinating underwater adhesion is largely attributed to their proteinaceous secretions containing special chemical functionalities such as 3,4-dihydroxyphenyllalanine (DOPA). , DOPA, due to its benzene ring connecting two neighboring hydroxy groups, allows for various noncovalent and covalent interactions with diverse surfaces even in the presence of hydration layer. , With this excellent surface affinity/adaptability, myriad DOPA-containing polymeric adhesives with favorable underwater adhesion have been developed. Additional chemical functionalities such as hydrophobicity and positive charges (cations) are often incorporated with DOPA to assist repelling the hydration layer. Although this mussel-inspired dehydrating strategy can bestow synthetic adhesives with strong underwater adhesion, the intrinsic tendency to oxidation undermines the robustness of DOPA-based adhesives. , …”
Section: Introductionmentioning
confidence: 99%